Prevalence of Mastitis Pathogens and Antimicrobial Susceptibility of Isolates From Cattle and Buffaloes in Northwest of Pakistan - Ali, Tariq; Kamran,; Raziq, Abdur; Wazir, Inamullah; Ullah, Rafi; Shah, Pervaiz; Ali, Muhammad Ijaz; Han, Bo; Liu, Gang (Frontiers in Veterinary Science, 2021)
Mastitis is the most prevalent disease of dairy animals, imparting huge economic losses to the dairy industry. There is always a dire need to monitor the prevalence of mastitis, its bacteriology, and evaluation of antimicrobial susceptibilities for mastitis control and prevention. Therefore, the objectives of this study were to investigate: (i) the prevalence of mastitis in cattle and buffaloes; (ii) identification of bacteria associated with mastitis; (iii) antimicrobial susceptibility of bacterial isolates. Milk samples (n = 1,566) from cattle (n = 1,096) and buffaloes (n = 470) were processed for detection of mastitis using the California mastitis test in the year 2018–19. A total of 633 mastitic milk samples were further processed for bacteriology and antimicrobial susceptibility testing by the disc diffusion method. Overall, the prevalence of clinical and subclinical mastitis was 17 and 57% in both species. Clinical mastitis was higher in cattle (20%) compared to buffaloes (11%), whereas subclinical was higher in buffaloes (66%) than cattle (53%). Besides, month-wise prevalence was higher in hot and humid months in both species. Staphylococci spp. (34%) were the most predominant bacterial isolates from mastitic milk, followed by Escherichia coli (19.4%), Streptococci spp. (9%), and Klebsiella spp. (8%). Most of the bacteria were susceptible to gentamicin (92%) and enrofloxacin (88%), when a panel of 16 different antimicrobials was tested. Nevertheless, most of the isolates were resistant to sulphamethoxazole (99%), lincomycin (98%), oxytetracycline (89%), ampicillin (86%), and doxycycline (85%). This study concludes a high prevalence of mastitis caused by Staphylococcal spp. in cattle and buffaloes belonging to the northwest of Pakistan, and gentamicin and enrofloxacin might be appropriate antimicrobial agents in the treatment of bovine mastitis.